Fe-Ce-Pt-based catalyst, preparation method and application thereof, and method for preparing olefin from synthesis gas
Through the preparation of Fe-Ce-Pt-based catalyst under specific calcining conditions, the problems of low activity and ease of inactivation of iron-based catalysts are solved, efficient CO conversion and C2+ olefin selectivity are achieved, process flow is simplified and olefins are improved Yield.
Patent Information
- Application Number
- CN202310874740.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The existing iron-based catalysts have low catalytic activity and are prone to inactivation in Fischer-Tropsch synthesis, resulting in a decrease in CO conversion and C2+ olefin selectivity, and the fluidized bed process is complex and the olefin yield is not high.
Using Fe-Ce-Pt-based catalyst, active components containing Fe, Ce and Pt are synthesized in the presence of an acid-base regulator, and a catalyst is formed under specific calcining conditions, for the Fischer-Tropsch reaction of the synthesis gas.
High CO conversion and C2+ olefin selectivity are achieved, and catalytic activity is maintained during long-term use, simplifying the process flow and improving the olefin yield.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a Fe-Ce-Pt based catalyst and a preparation method and application thereof, and a method for preparing olefins from synthesis gas. Background Art
[0002] The efficient conversion of syngas (mainly CO and H2) from a wide range of sources, mainly from coal gasification but not limited to coal gasification, into olefins is a major route in modern coal chemical industry. It can not only solve the problem of high pollution when coal is burned, but also improve my country's energy independence (my country's energy characteristics are more coal, less gas and oil, and strong dependence on energy imports). There are two methods for converting syngas into olefins: direct method and indirect method. The indirect method generally adopts the route from syngas to methanol and then to low-carbon olefins, while the Fischer-Tropsch process is one of the efficient routes for synthesizing olefins from syngas in one step.
[0003] Fischer-Tropsch synthesis refers to the process of directly synthesizing organic matter from synthesis gas under the action of a catalyst. It is divided into high-temperature Fischer-Tropsch (above 300°C) and low-temperature Fischer-Tropsch (200-280°C) according to different process conditions. It can be divided into fixed-bed Fischer-Tropsch, slurry-bed Fischer-Tropsch and fluidized-bed Fischer-Tropsch according to different types of reactors used. It can be divided into iron-based catalyst Fischer-Tropsch and cobalt-based catalyst Fischer-Tropsch according to different types of catalysts used. High-temperature Fischer-Tropsch generally adopts a fluidized bed process, and the catalyst mostly uses an iron-based catalyst. Its products are mainly low-carbon chain products with a C number ≤ 20, which are generally used to produce low-carbon olefins and gasoline and diesel. For example, patent CN1704161A mentions the preparation of an iron-based catalyst for Fischer-Tropsch synthesis, and patent CN1695804A introduces a precipitated iron catalyst for a fluidized bed. Low-temperature Fischer-Tropsch mostly uses fixed bed or slurry bed processes, and the catalysts include both cobalt-based catalysts (CN110252358A mentions a cobalt catalyst and its preparation method and a method for Fischer-Tropsch synthesis of Fischer-Tropsch wax) and iron-based catalysts (CN1113905A reports the preparation of a Fischer-Tropsch synthesis iron catalyst for a slurry bed reactor).
[0004] At present, there are some attempts to apply fixed bed to high temperature Fischer-Tropsch for olefin production. However, since Fischer-Tropsch synthesis is a highly exothermic reaction, it is difficult to remove heat from the reactor when using a fixed bed, which can easily cause the temperature to rise and the catalyst to deactivate. During long-term operation, the CO conversion rate and C2 + The olefin selectivity will be reduced. The fluidized bed can effectively overcome the heat release problem of the fixed bed, but it still has the disadvantages of complex process (because the catalyst needs to be reduced before the synthesis reaction, the reduction conditions are very different from the synthesis reaction conditions, so in addition to the reactor and the subsequent separation system, a reactor for reduction is also provided) and low olefin yield. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of low catalytic activity and easy deactivation of the iron-based catalyst in the prior art, and to provide a new Fe-Ce-Pt-based catalyst and its preparation method and application, and a method for preparing olefins from synthesis gas. The catalyst is easy to deactivate during reuse and has excellent catalytic activity.
[0006] The first aspect of the present invention provides a Fe-Ce-Pt based catalyst, which comprises the following components: A) a carrier; B) a catalyst having a general formula of Fe 100 A a Ce b Pt 0.01b O x Active components, wherein A is selected from at least one of VB group metal elements, IVB group metal elements and VIB group metal elements; a=5-50; b=1-10; x is the total number of oxygen atoms required to satisfy the valence of each element in the active component; and the molar ratio of Ce to Pt on the catalyst surface is 100:5-8, calculated on the basis of elements.
[0007] The second aspect of the present invention provides a method for preparing the Fe-Ce-Pt-based catalyst of the present invention, which comprises: in the presence of an acid-base regulator, contacting a solution I containing a Fe source and a Ce source, a Pt source solution, and a solution II containing a carrier source and a source A to obtain a slurry, followed by drying, optionally forming, performing a first calcination in an oxygen-containing atmosphere I, and performing a second calcination in an oxygen-containing atmosphere II mixed with water vapor; wherein the water content in the oxygen-containing atmosphere I and the oxygen-containing atmosphere II is not more than 1 ppm respectively.
[0008] The third aspect of the present invention provides use of the Fe-Ce-Pt based catalyst of the present invention in preparing olefins from synthesis gas.
[0009] A fourth aspect of the present invention provides a method for preparing olefins from synthesis gas, the method comprising: contacting the synthesis gas with a catalyst to carry out a Fischer-Tropsch reaction.
[0010] Through the above technical scheme, the catalyst of the present invention is used in the preparation of olefins from synthesis gas, has the characteristics of high raw material conversion rate and high target product conversion rate, and can maintain excellent catalytic activity during long-term use. DETAILED DESCRIPTION
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0012] The first aspect of the present invention provides a Fe-Ce-Pt based catalyst, which comprises the following components: A) a carrier; B) a catalyst having a general formula of Fe 100 A a Ce b Pt 0.01b O x Active components, wherein A is selected from at least one of VB group metal elements, IVB group metal elements and VIB group metal elements; a=5-50; b=1-10; x is the total number of oxygen atoms required to satisfy the valence of each element in the active component; and the molar ratio of Ce to Pt on the catalyst surface is 100:5-8, calculated on the basis of elements.
[0013] In the present invention, the element analysis parameters of the catalyst surface are measured by the XPS characterization method.
[0014] The present invention provides a new Fe-Ce-Pt based catalyst, in which specific active components and carriers cooperate with each other, and a specific ratio of Ce to Pt on the catalyst surface makes the catalyst have excellent catalytic activity. When the catalyst is used in the reaction of preparing olefins from synthesis gas, not only CO has a high conversion rate, but also C2 + The catalyst has high selectivity for olefins, and during long-term operation, the catalyst can maintain good catalytic activity and high selectivity for C2+ olefins.
[0015] In the present invention, it is understood that by the general formula Fe 100 A a Ce b Pt 0.01b O x The molar content ratio of Fe, A, Ce and Pt in the active components can be obtained as 100:a:b:0.01b, which does not represent their actual molar content in the catalyst, for example, a=100 / molar content of Fe in the catalyst*molar content of A in the catalyst.
[0016] In the present invention, the molar ratio of Ce to Pt on the catalyst surface is detected by XPS.
[0017] According to a preferred embodiment of the present invention, a=8-45, for example, 8, 10, 15, 20, 30, 35, 45, or a range consisting of any two of the above values. The catalyst of this embodiment has better catalytic activity. When the catalyst is used in the reaction of preparing olefins from synthesis gas, C2 + It has high selectivity for olefins and can maintain excellent catalytic activity during long-term use.
[0018] According to a preferred embodiment of the present invention, b=2-8, for example, 2, 3, 4, 5, 6, 7, 8, or a range consisting of any two of the above values. The catalyst of this embodiment has better catalytic activity. When the catalyst is used in the reaction of preparing olefins from synthesis gas, C2 + It has high selectivity for olefins and can maintain excellent catalytic activity during long-term use.
[0019] According to a preferred embodiment of the present invention, A is selected from VB group metal elements, preferably at least one of V, Nb and Ta, and more preferably V. The catalyst components of this embodiment have better synergistic effects. When the catalyst is used in the reaction of preparing olefins from synthesis gas, C2 + It has high selectivity for olefins and can maintain excellent catalytic activity during long-term use.
[0020] According to a preferred embodiment of the present invention, A is V. The various components in the catalyst of this embodiment have better synergy, can better form specific lattice defects in the catalyst, and the catalyst has better catalytic activity. When the catalyst is used in the reaction of preparing olefins from synthesis gas, C2 + It has high selectivity for olefins and can maintain excellent catalytic activity during long-term use.
[0021] According to a preferred embodiment of the present invention, in the catalyst, the carrier content is 60-80 wt% of the catalyst mass.
[0022] According to the present invention, as long as the purpose of the present invention can be achieved, the content of active components in the catalyst is not particularly limited. According to a preferred embodiment of the present invention, the content of the active components is 20-40w% of the catalyst mass in terms of oxide.
[0023] According to a preferred embodiment of the present invention, the carrier is selected from oxides of Si and / or Al. In the catalyst of this embodiment, the carrier and the active component can better cooperate with each other, thereby increasing the activity of the catalyst and the C2 + Olefin selectivity.
[0024] In the present invention, as long as the purpose of the present invention can be achieved, the method for preparing the Fe-Ce-Pt-based catalyst of the present invention is not particularly limited. Preferably, the second aspect of the present invention provides a method for preparing the Fe-Ce-Pt-based catalyst of the present invention, which comprises: in the presence of an acid-base regulator, a solution I containing a Fe source and a Ce source, a Pt source solution, and a solution II containing a carrier source and a source A are contacted to obtain a slurry, followed by drying, optionally forming, performing a first calcination in an oxygen-containing atmosphere I, and performing a second calcination in an oxygen-containing atmosphere II mixed with water vapor; wherein the water content in the oxygen-containing atmosphere I and the oxygen-containing atmosphere II is not more than 1 ppm respectively.
[0025] In the present invention, it can be understood that the water vapor mixed in the oxygen-containing atmosphere II mixed with water vapor does not include the water vapor that may be contained in the oxygen-containing atmosphere II.
[0026] In the present invention, the preparation method of the present invention can be used to prepare a specific catalyst with a molar ratio of Ce to Pt on the catalyst surface of 100:5-8, and in the specific calcination environment of the first calcination and the second calcination of the present invention, a catalyst with specific lattice defects can be formed. The catalyst has high catalytic activity in the preparation of olefins from synthesis gas, and C2 + The catalyst has high selectivity for olefins and can maintain excellent catalytic activity during long-term use.
[0027] According to the present invention, as long as the purpose of the present invention can be achieved, the specific selection of the oxygen-containing atmosphere I and the oxygen-containing atmosphere II is not particularly limited. According to a preferred embodiment of the present invention, the oxygen-containing atmosphere I and the oxygen-containing atmosphere II are each independently oxygen and / or air. Based on cost considerations, in the present invention, the oxygen-containing atmosphere I and the oxygen-containing atmosphere II are both selected from air, but the present invention is not limited thereto.
[0028] According to a preferred embodiment of the present invention, the conditions for the first calcination include: a temperature of 500-900°C, preferably 550-850°C. The catalyst obtained by adopting this embodiment has better catalytic activity. When it is used in the preparation of olefins from synthesis gas, CO has a higher conversion rate, and C2 + The selectivity for olefins is high.
[0029] According to a preferred embodiment of the present invention, the conditions for the first calcination include: a time of 0.5-5 h, preferably 1-4 h.
[0030] According to a preferred embodiment of the present invention, in the second calcination, the volume ratio of water vapor to oxygen-containing atmosphere II is 1-5:100, for example, 1:100, 2:100, 3:100, 4:100, 5:100, or a range consisting of any two of the above ratios. The catalyst with specific lattice defects can be obtained by using this embodiment, which has high catalytic activity. When used in synthesis gas to olefins, CO has a higher conversion rate, and C2 + The selectivity for olefins is high.
[0031] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a temperature of 550-850°C, preferably 580-830°C. The catalyst obtained by adopting this embodiment has better catalytic activity. When it is used in the preparation of olefins from synthesis gas, CO has a higher conversion rate, and C2 + The selectivity for olefins is high.
[0032] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a time of 0.2-2 h, preferably 0.5-1.8 h.
[0033] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the acid-base regulator added is not particularly limited. According to a preferred embodiment of the present invention, the amount of the acid-base regulator added is to adjust the pH value of the slurry to 1-5 (for example, 1, 2, 3, 4, 5, or a range consisting of any two of the above values).
[0034] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the acid-base regulator is not particularly limited, as long as the slurry can be adjusted to a desired pH value, for example, it can be ammonia water with a concentration of 10-40wt%.
[0035] According to a preferred embodiment of the present invention, the solid content of the slurry is 15-45% by weight.
[0036] According to a preferred embodiment of the present invention, the contacting conditions include: a temperature of 40-80° C., and optional supplementation of water.
[0037] According to the present invention, optionally supplementing water means that water may be supplemented or not supplemented during contacting as required. In the present invention, water may be selectively supplemented during contacting according to the solid content of the slurry.
[0038] According to the present invention, the contact is preferably a dynamic contact, such as by stirring and beating.
[0039] According to the present invention, it can be understood that the solution I containing the Fe source and the Ce source refers to the solution I obtained by mixing raw materials such as the Fe source and the Ce source with the corresponding good solvent. There is no special limitation on the total content of the Fe source and the Ce source in the solution I, as long as the Fe source and the Ce source can be completely dissolved. For example, in terms of Fe and Ce elements, the content of the Fe source and the Ce source in the solution I is 0.1-1 mol / L; wherein, the good solvent for dissolving the Fe source and the Ce source can be any solvent in the art, such as water; in the specific preparation, the Fe source and the Ce source can be co-dissolved in water to obtain the solution I containing the Fe source and the Ce source.
[0040] According to the present invention, it can be understood that the Pt source solution refers to a solution obtained by mixing a Pt source with a corresponding good solvent, and the content of the Pt source in the solution is not particularly limited as long as the Pt source can be completely dissolved; for example, the content of the Pt source in the Pt source solution is 1-10 mg / ml in terms of metallic Pt; wherein the type of the good solvent is not limited, for example, it is water.
[0041] According to the present invention, solution II containing a carrier source and a source A refers to a solution of raw materials such as a carrier source, a source A and a corresponding good solvent. The method for obtaining solution II containing a carrier source and a source A may be any method in the art. Preferably, the method for obtaining solution II containing a carrier source and a source A comprises: dissolving the source A in a good solvent to obtain a solution II-1, and then mixing the carrier source with the solution II-1 to obtain a solution II. As long as the purpose of the present invention can be achieved, the type of the good solvent is not limited, and is generally water.
[0042] In the present invention, unless otherwise specified, the good solvent in solution I, the Pt source solution and solution II is water.
[0043] In the present invention, the amount of the good solvent in solution I, solution II and Pt source is not particularly limited, as long as it can dissolve the corresponding raw material sources in the system; when preparing the corresponding solutions, in order to make the corresponding raw material sources dissolve more efficiently in the good solvent, the dissolution can be carried out at a certain temperature, for example, at 50-100°C.
[0044] According to a preferred embodiment of the present invention, the carrier source is selected from a sol containing SiO2 and / or Al2O3. The catalyst obtained in this embodiment has high catalytic activity and stability.
[0045] In the present invention, when preparing the corresponding catalyst, the specific amounts of Fe source, Fe source, Ce source, A source, Pt source and carrier source are not particularly limited and can be selected according to the amounts of active components in the corresponding catalyst, which will not be elaborated herein.
[0046] In the present invention, there is no limitation on the types of Fe source, Ce source, A source and Pt source, as long as they can provide the corresponding elements, and they may be chlorides, nitrates and inorganic ammonium salts of the corresponding elements; according to one embodiment of the present invention, the Fe source is selected from at least one of nitrates, citrates, chlorides and nitrites of Fe; according to one embodiment of the present invention, the Ce source is selected from at least one of nitrates, citrates and chlorides of Ce; according to one embodiment of the present invention, the Pt source is selected from nitrates and / or chlorides of Pt; according to one embodiment of the present invention, the A source is selected from ammonium salts and / or nitrates of A.
[0047] According to the present invention, there is no special limitation on the drying method for preparing the Fe-Ce-Pt-based catalyst, for example, a spray dryer can be used for spray drying; optional molding means that molding can be selected or not selected as needed, and when a spray dryer is used for drying, the solid matter in the slurry can be directly dried and molded into a microsphere, that is, it is molded during the drying process, and can be selected or not to be molded again as needed later.
[0048] According to the present invention, only the purpose of the present invention can be achieved, and the conditions when using a spray dryer for drying are not particularly limited, for example, the inlet temperature of the spray dryer is 300-350°C, and / or the outlet temperature is 170-230°C.
[0049] The third aspect of the present invention provides use of the Fe-Ce-Pt based catalyst of the present invention in preparing olefins from synthesis gas.
[0050] The novel Fe-Ce-Pt-based catalyst provided by the present invention has unique properties and can be used in the preparation of olefins from synthesis gas, and has high catalytic activity and can obtain high CO conversion rate and C2 + The catalyst has high olefin selectivity and can maintain high catalytic activity during long-term use.
[0051] A fourth aspect of the present invention provides a method for preparing olefins from synthesis gas, the method comprising: contacting the synthesis gas with a catalyst to carry out a Fischer-Tropsch reaction.
[0052] The novel Fe-Ce-Pt-based catalyst provided by the present invention has unique properties and can be used in the Fischer-Tropsch reaction of preparing olefins from synthesis gas to obtain high CO conversion rate and C2 + The catalyst has high olefin selectivity and can maintain high catalytic activity during long-term use.
[0053] When the Fe-Ce-Pt-based catalyst of the present invention is used in the Fischer-Tropsch reaction of preparing olefins from synthesis gas, it may be reduced or not before the reaction. Preferably, it is reduced first. More preferably, the reduction treatment conditions include: preferably in H2 atmosphere, preferably at a temperature of 280-400°C, preferably at a pressure of normal pressure-8.0 MPa, and preferably at a standard volume space velocity of 2000-12000 h -1 , the preferred reduction time is 3-480 hours.
[0054] According to a preferred embodiment of the present invention, the synthesis gas includes CO and H2, and preferably the volume ratio of CO to H2 is 1:0.5-2.
[0055] According to the present invention, as long as the purpose of the present invention can be achieved, the conditions of the Fischer-Tropsch reaction are not particularly limited. According to a preferred embodiment of the present invention, the conditions of the Fischer-Tropsch reaction include: a reaction temperature of 280-380°C.
[0056] According to a preferred embodiment of the present invention, the conditions of the Fischer-Tropsch reaction include: a reaction pressure of 0.5-8.0 MPa.
[0057] According to a preferred embodiment of the present invention, the conditions of the Fischer-Tropsch reaction include: a standard volume space velocity of 2000-12000 hours -1 .
[0058] The present invention will be described in detail below through examples. In the following examples and comparative examples, the elemental analysis parameters of the catalyst surface are measured by XPS characterization method;
[0059] In the following examples and comparative examples, the water content in the air is less than 1 ppm, and the water vapor content in the atmosphere of a certain ratio of water vapor to air does not include the water vapor less than 1 ppm that may be contained in the air.
[0060] In the present invention, C2 + Olefins are olefins having 2 to 20 carbon atoms, C2 + Total carbon number of olefins / total carbon number of organic matter in the product = C2 + The total carbon number of olefins / the total carbon number of organic matter in the product + the total carbon number of CO2 in the product.
[0061] Example 1
[0062] 1) Catalyst preparation:
[0063] Dissolve 35.1g of NH4VO3 in 100℃ water to prepare 0.5mol / L element V solution Ⅰ;
[0064] 675 g of silica sol (containing 40 wt% SiO2) was mixed with solution I to obtain a mixed solution II;
[0065] Dissolve 404 g of Fe(NO3)3·9H2O and 21.7 g of Ce(NO3)3·6H2O in water to prepare a 0.5 mol / L mixed solution III of Fe and Ce elements;
[0066] Add mixed solution III and 5 mg / ml PtCl4 solution containing 0.0005 mol of Pt element in terms of metal Pt into mixed solution II, stir and slurry at 48° C., adjust the pH value of the mixture to 5 with 25 wt % ammonia water, and adjust the solid content of the mixture to 35% with water to obtain slurry IV;
[0067] The slurry was spray dried to form, the inlet temperature of the spray machine was 320°C, and the outlet temperature was 190°C to obtain a spray dried material; the spray material was first calcined at 800°C in an air atmosphere for 1 hour, and then calcined at 750°C for 0.5 hour in an atmosphere of water vapor: air = 3:100 to obtain a catalyst.
[0068] The composition of the catalyst is: 30wt%Fe 100 V 30 Ce5P 0.05 O x +70wt%SiO2.
[0069] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:6.
[0070] 2) Catalyst evaluation:
[0071] The catalyst is reduced by an in-situ reduction method, and after the reduction is completed, the process conditions are directly switched to synthetic reaction conditions in the reactor used for the reduction to start the reaction;
[0072] Reactor Specifications: mm fluidized bed reactor;
[0073] Catalyst loading: 50 g;
[0074] The reduction conditions are: temperature 350°C;
[0075] Pressure 0.8MPa
[0076] Catalyst loading (standard volume space velocity) 4000 hours -1 ;
[0077] Reducing gas H2;
[0078] Restoration time: 12 hours;
[0079] The synthetic reaction conditions are: reaction temperature 350°C;
[0080] Reaction pressure 1.1MPa;
[0081] Catalyst loading (standard volume space velocity) 4000 hours -1 ;
[0082] The raw material ratio (molar) in the synthesis gas is CO / H2=1:1;
[0083] When the reaction was run for 100 h, the CO conversion rate was 92%, and the C2 + The selectivity to olefins (including CO2) is 63%;
[0084] When the reaction was run for 2000h, the CO conversion rate was 94%, and the C2 + The selectivity to olefins (including CO2) was 62%.
[0085] Example 2
[0086] 1) Catalyst preparation:
[0087] Dissolve 52.7g of NH4VO3 in 100℃ water to prepare 0.5mol / L element V solution Ⅰ;
[0088] 754 g of aluminum sol (Al2O3 content 40 wt%) was mixed with solution I to obtain mixed solution II;
[0089] Dissolve 404g of Fe(NO3)3·9H2O and 34.7g of Ce(NO3)3·6H2O in water to prepare a 0.5mol / L mixed solution III of Fe and Ce elements;
[0090] Add mixed solution III and 5 mg / ml PtCl4 solution containing 0.0008 mol of Pt element in terms of metal Pt into mixed solution II, stir and slurry at 48° C., adjust the pH value of the mixture to 5 with 25 wt % ammonia water, and adjust the solid content of the mixture to 35% with water to obtain slurry IV;
[0091] The slurry was spray dried to obtain a spray dried material with the spray machine inlet temperature at 320°C and outlet temperature at 190°C. The spray dried material was first calcined at 850°C for 0.8h in an air atmosphere and then calcined at 800°C for 0.5h in an atmosphere of steam: air = 2:100 to obtain a catalyst.
[0092] The composition of the catalyst is: 30wt%Fe 100 V 45 8P 0.08 O x +70wt%SiO2.
[0093] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:5.6.
[0094] 2) Catalyst evaluation:
[0095] The catalyst is reduced by an in-situ reduction method, and after the reduction is completed, the process conditions are directly switched to synthetic reaction conditions in the reactor used for the reduction to start the reaction;
[0096] Reactor Specifications: mm fluidized bed reactor;
[0097] Catalyst loading: 50 g;
[0098] The reduction conditions are: temperature 350°C;
[0099] Pressure: 0.8MPa;
[0100] Catalyst loading (standard volume space velocity) 4000 hours -1 ;
[0101] Reducing gas H2;
[0102] Restoration time: 12 hours;
[0103] The synthetic reaction conditions are: reaction temperature 350°C;
[0104] Reaction pressure 1.1MPa;
[0105] Catalyst loading (standard volume space velocity) 4000 h-1;
[0106] The raw material ratio (molar) in the synthesis gas is CO / H2=1:1.
[0107] When the reaction was run for 100 h, the CO conversion rate was 91%, and the C2 + The selectivity to olefins (including CO2) is 64%;
[0108] When the reaction was run for 2000h, the CO conversion rate was 93%, and the C2 + The selectivity to olefins (including CO2) was 63%.
[0109] Example 3
[0110] 1) Catalyst preparation:
[0111] Dissolve 29.3g of NH4VO3 in 100℃ water to prepare 0.5mol / L element V solution Ⅰ;
[0112] 807 g of silica sol (SiO2 content 40 wt%) was mixed with solution I to obtain mixed solution II;
[0113] Dissolve 404 g of Fe(NO3)3·9H2O and 13.0 g of Ce(NO3)3·6H2O in water to prepare a 0.5 mol / L mixed solution III of Fe and Ce elements;
[0114] The mixed solution III and a 5 mg / ml PtCl4 solution containing 0.0003 mol of Pt element in terms of metallic Pt are added to the mixed solution II, and the mixture is stirred and slurried at 55°C. At the same time, the pH value of the mixture is adjusted to 5 with 25 wt% ammonia water, and the solid content of the mixture is adjusted to 30% with water to obtain slurry IV; the slurry is spray-dried and formed, the inlet temperature of the sprayer is 300°C, and the outlet temperature is 175°C to obtain a spray-dried material; the spray material is first calcined at 750°C in an air atmosphere for 2.5 h, and then calcined at 780°C for 1 h in an atmosphere of water vapor: air = 4:100 to obtain a catalyst.
[0115] The composition of the catalyst is: 25wt%Fe 100 V 25 Ce3Pt 0.03 O x +75wt%SiO2.
[0116] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:6.4.
[0117] 2) Catalyst evaluation:
[0118] The catalyst is reduced by an in-situ reduction method, and after the reduction is completed, the process conditions are directly switched to synthetic reaction conditions in the reactor used for the reduction to start the reaction;
[0119] Reactor Specifications: mm fluidized bed reactor;
[0120] Catalyst loading: 50 g;
[0121] The reduction conditions are: temperature 350°C;
[0122] Pressure: 0.8MPa;
[0123] Catalyst loading (standard volume space velocity) 4000 hours - 1 ;
[0124] Reducing gas H2;
[0125] Restoration time: 12 hours;
[0126] The synthetic reaction conditions are: reaction temperature 350°C;
[0127] Reaction pressure 1.1MPa;
[0128] Catalyst loading (standard volume space velocity) 4000 hours -1 ;
[0129] The raw material ratio (molar) in the synthesis gas is CO / H2=1:1;
[0130] When the reaction was run for 100 h, the CO conversion rate was 90%, and the C2 + The selectivity to olefins (including CO2) is 62%;
[0131] When the reaction was run for 2000h, the CO conversion rate was 93%, and the C2 + The selectivity to olefins (including CO2) was 61%.
[0132] Example 4
[0133] The catalyst was prepared and evaluated according to the method of Example 3, except that the spray-dried material was first calcined at 750°C for 2.5 h in an air atmosphere, and then calcined at 780°C for 1 h in an atmosphere of steam: air = 7:100. The remaining steps were the same as in Example 3, and finally the catalyst was prepared.
[0134] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:7.8.
[0135] When the reaction was run for 100 h, the CO conversion was 89% and the selectivity of C2+ olefins (including CO2) was 55%;
[0136] When the reaction was run for 2000 h, the CO conversion rate was 87% and the selectivity of C2+ olefins (including CO2) was 52%.
[0137] Example 5
[0138] The catalyst was prepared and evaluated according to the method of Example 3, except that 807 g of titanium sol (TiO2 content 40 wt%) was used to replace 807 g of silica sol (SiO2 content 40 wt%). The remaining steps were the same as Example 3, and the catalyst was finally prepared.
[0139] The composition of the catalyst is: 25wt%Fe 100 V 25 Ce3Pt 0.03 O x +75wt%TiO2.
[0140] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:4.5.
[0141] When the reaction was run for 100 h, the CO conversion rate was 84%, and the C2 + The selectivity to olefins (including CO2) is 59%;
[0142] When the reaction was run for 2000h, the CO conversion rate was 82%, and the C2 + The selectivity to olefins (including CO2) was 57%.
[0143] Example 6
[0144] The catalyst was prepared and evaluated according to the method of Example 3, except that 44.2 g of (NH4)6Mo7O 24 The solution was dissolved in water to prepare a 0.5 mol / L Mo element solution I, and the remaining steps were the same as those in Example 3 to finally prepare the catalyst.
[0145] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:6.9.
[0146] When the reaction was run for 100 h, the CO conversion was 89% and the selectivity of C2+ olefins (including CO2) was 59%;
[0147] When the reaction was run for 2000 h, the CO conversion rate was 88% and the selectivity of C2+ olefins (including CO2) was 56%.
[0148] Example 7
[0149] The catalyst was prepared and evaluated according to the method of Example 3, except that: 8.2 g of NH4VO3 was dissolved in 100°C water to prepare a 0.5 mol / L V element solution I; 778 g of silica sol (SiO2 content 40 wt%) was mixed with solution I to obtain a mixed solution II; 404 g of Fe(NO3)3·9H2O and 43.5 g of Ce(NO3)3·6H2O were co-dissolved in water to prepare a 0.5 mol / L mixed solution III of Fe and Ce elements; mixed solution III and a 5 mg / ml PtCl4 solution containing 0.001 mol of Pt element in terms of metallic Pt were added to mixed solution II and stirred and slurried at 55°C. The remaining steps were the same as in Example 3, and the catalyst was finally prepared.
[0150] The composition of the catalyst is: 25wt%Fe 100 VxD 10 Pt 0.1 O x +75wt%TiO2.
[0151] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:7.2.
[0152] When the reaction was run for 100 h, the CO conversion rate was 89%, and the C2 + The selectivity to olefins (including CO2) is 59%;
[0153] When the reaction was run for 2000h, the CO conversion rate was 88%, and the C2 + The selectivity to olefins (including CO2) was 56%.
[0154] Comparative Example 1
[0155] The catalyst was prepared and evaluated according to the method of Example 3, except that the spray-dried material was first calcined at 750°C for 2.5 h in an air atmosphere and then continued to be calcined at 780°C for 1 h in an air atmosphere. The remaining steps were the same as Example 3, and the catalyst was finally prepared.
[0156] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:2.
[0157] When the reaction was run for 100 h, the CO conversion rate was 30%, and the C2 + The selectivity to olefins (including CO2) was 35%.
[0158] Comparative Example 2
[0159] The catalyst was prepared and evaluated according to the method of Example 3, except that the spray-dried material was first calcined at 750°C for 2.5 h in an atmosphere of water vapor: air = 3:100, and then continued to be calcined at 780°C for 1 h in an atmosphere of water vapor: air = 4:100. The remaining steps were the same as in Example 3, and the catalyst was finally prepared.
[0160] XPS analysis showed that the molar ratio of Ce to Pt on the surface of the prepared catalyst was 100:9.
[0161] When the reaction was run for 100 h, the CO conversion rate was 95%, and the C2 + The selectivity to olefins (including CO2) was 19%.
[0162] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A Fe-Ce-Pt based catalyst, characterized in that: The catalyst contains the following components: A) carrier; B) In terms of atomic ratio, the general formula is Fe 100 A a Ce b Pt 0.01b O x The active ingredient, Wherein, A is selected from at least one of VB group metal elements, IVB group metal elements and VIB group metal elements; a=5-50; b=1-10; x is the total number of oxygen atoms required to satisfy the valence of each element in the active component; Calculated by elements, the molar ratio of Ce to Pt on the catalyst surface is 100:5-8.
2. The catalyst according to claim 1, wherein a=8-45;and / or b = 2-8; and / or A is selected from VB group metal elements, preferably at least one of V, Nb and Ta, and more preferably V.
3. The catalyst according to claim 1 or 2, wherein In the catalyst, the carrier content is 60-80wt% of the catalyst mass; and / or The active component content is 20-40wt% of the catalyst mass, calculated as oxide; and / or The support is selected from oxides of Si and / or Al.
4. A method for preparing the Fe-Ce-Pt based catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: In the presence of an acid-base regulator, a solution I containing a Fe source and a Ce source, a Pt source solution, and a solution II containing a carrier source and a A source are contacted to obtain a slurry, which is then dried, optionally formed, and subjected to a first calcination in an oxygen-containing atmosphere I, and a second calcination in an oxygen-containing atmosphere II mixed with water vapor; wherein the water content in the oxygen-containing atmosphere I and the oxygen-containing atmosphere II is not more than 1 ppm respectively.
5. The preparation method according to claim 4, wherein The conditions of the first calcination include: a temperature of 500-900° C., preferably 550-850° C.; and / or a time of 0.5-5 h, preferably 1-4 h; and / or In the second calcination, the volume ratio of water vapor to oxygen-containing atmosphere II is 1-5:100; and / or The conditions for the second calcination include: a temperature of 550-850° C., preferably 580-830° C.; and / or a time of 0.2-2 h, preferably 0.5-1.8 h; and / or The oxygen-containing atmosphere I and the oxygen-containing atmosphere II are each selected from air and / or oxygen.
6. The preparation method according to claim 4 or 5, wherein: The amount of the acid-base regulator added is such that the pH value of the slurry is 1-5; and / or The solid content of the slurry is 15-45% by weight; and / or The contacting conditions include: a temperature of 40-80° C., and optional supplementation of water.
7. The preparation method according to any one of claims 4 to 6, wherein: The carrier source is selected from a sol containing SiO2 and / or Al2O3; and / or The Fe source is selected from at least one of nitrate, citrate, chloride and nitrite of Fe; and / or The Ce source is selected from at least one of nitrate, citrate and chloride of Ce; and / or The Pt source is selected from nitrates and / or chlorides of Pt; and / or The A source is selected from the ammonium salt and / or nitrate salt of A.
8. Use of the Fe-Ce-Pt based catalyst according to claim 1 or 2 in preparing olefins from synthesis gas.
9. A method for preparing olefins from synthesis gas, characterized in that: The method comprises: contacting synthesis gas with a catalyst to carry out Fischer-Tropsch reaction; wherein the catalyst is the catalyst according to claim 1 or 2.
10. The preparation method according to claim 9, wherein: The synthesis gas comprises CO and H2, preferably the volume ratio of CO to H2 is 1:0.5-2; and / or The method further comprises reducing the catalyst before use, and the reduction conditions preferably include: under H2 atmosphere; and / or at a temperature of 280-400°C; and / or at a pressure of normal pressure-8.0 MPa; and / or at a standard volume space velocity of 2000-12000 h -1 ; and / or a reduction time of 3-480 hours; and / or The conditions of the Fischer-Tropsch reaction include: a reaction temperature of 280-380°C; and / or a reaction pressure of 0.5-8.0 MPa; and / or a standard volume space velocity of 2000-12000 hours -1 .
Citation Information
Patent Citations
Fischer-Tropsch synthesis cobalt catalyst and preparation method thereof, and Fischer-Tropsch synthesis method
CN110252358A
Process for the production of hydrocarbons
CN1113905A
Microsphere shaped iron based catalyst in use for Fischer-Tropsch synthesis under high temperature, and preparation method
CN1695804A
Sintered iron catalyst for Fischer-Tropsch Synthesis and preparation method and application thereof
CN1704161A
Iron-based catalyst for synthesizing low carbon olefin, and preparation method thereof
CN104107699A